The effects of gender and country of origin on acculturation, psychological factors, lifestyle factors, and diabetes-related physiological outcomes among Mexican Americans: The Starr County diabetes prevention initiative. (June 2023) - Brown, Sharon A; Becker, Heather A; García, Alexandra A; Velasquez, Mary M; Tanaka, Hirofumi; Winter, Mary A; Perkison, William B; Brown, Eric L; Aguilar, David; Hanis, Craig L
Objectives: Examine acculturation and psychological, lifestyle, and physiological factors based on gender and country of origin (U.S. vs. Mexico). Methods: Baseline data from the Starr County diabetes prevention study ( N = 300) were analyzed – acculturation ( language ), psychological factors ( depression ), lifestyle factors ( sedentary behaviors ), and diabetes-related physiological outcomes ( insulin resistance ). MANOVA and linear regression were used to examine variable relationships based on gender and country of origin and identify predictors of depression and insulin resistance. Results: Participants were: predominantly female (73%); 51 years of age, on average; born in Mexico (71%); and Spanish-speaking. Individuals spent 11 of their waking hours (range = 0–18 h) in sedentary activities. Compared to females, more males spoke English and reported fewer hours in sedentary activities. Compared to participants born in Mexico, those born in the U.S. were more likely to: speak English; report depressive symptoms; and exhibit elevated BMI and insulin resistance rates. Two distinct models significantly predicted depression (R 2 = 14.5%) and insulin resistance (R 2 = 26.8%), with acculturation-language entering into both models. Discussion: Significant gender and country-of-origin differences were found. Future research on diabetes prevention should examine other Hispanic subgroups and strategies for addressing individual differences, while employing cost-effective group interventions that incorporate these differences and reach more at-risk individuals.